Institutional and livelihood changes in East African forest landscapes decentralization and institutional change for sustainable forest management in Uganda, Kenya, Tanzania and Ethiopia (New York Peter Lang, 2013)
This book presents research articles and essays which analyze the consequences of decentralization on forest conditions and livelihoods in Uganda, Kenya, Tanzania and Ethiopia. Authors from the East African collaborative research centers of the International Forestry Resources and Institutions (IFRI) Research Program demonstrate that the institutional changes resulting from decentralization create costs for those who need to re-institutionalize and re-organize the management of forest and land resources. This requires investment into information, communication, education and into the re-building of social capital. Cases in which collective action has worked and contributed to improving livelihoods and forest conditions can be exemplary, while failures can be equally useful for learning about East Africa and beyond.
Keywords: Forest management -Africa, Eastern